Socio-economic history of Bade Emirate : 1825-1945 - Abdul, Jarma Yusuf (Kulliyyah Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research examines the socio-economic history of Bade Emirate from 1825 to 1945, the major factors that encouraged various economic activities and made them profitable during the pre-colonial times, and the reasons that led to the economic activities' decline. To achieve the goals of this research, a qualitative method based on historical approach, was adopted. The study found that there is no study of this nature that has been conducted on the economic history of Bade Emirate. The research highlighted the factors such as security and harmony within the emirate, the presence of Kumadugu Yobe River, fertile land, and vegetation as the key elements behind the success of the economic activities in the pre-colonial Bade Emirate. The research suggests that the colonial policies implemented by the British against local industrial production in Bade Emirate since 1904 was to block competition and, consequently, to achieve its goal of tapping enough raw materials and maintaining cheap markets for its finished goods. Thus, the British has achieved its goal at a very high price, which had been paid by the local people in Africa.The British colonialization of the Bade Emirate completely destroyed the local traditional industries and economic activities. African countries, which were enjoying economic sustainability and well-established manufacturing system before the arrival of the colonial powers, as the research found, are still suffering from the ills created by their civilized masters.At the end, the research suggests that Nigerian administration at both state and federal levels should trace back to history and revive these precolonial economic activities in a reformed and modernized shape, and encourage and assist the youth to be engaged in these activities in order to decrease existing poverty and social ills in the country.